Makna Perayaan Ekaristi Terhadap Pemulihan Korban Adiksi Narkoba di Rehabilitasi ‘Rumah Kita’ - Liana Sianturi (Divinitas Jurnal Filsafat dan Teologi Kontekstual, 2025)
Drug addicts are typically considered as morally, spiritually, and physically shattered individuals. Pastoral care is provided through the existence of the KSSY-managed drug recovery clinic "Rumah Kita." According to the research question, partaking in the Eucharist is a holistic approach to drug addiction recovery. Using a descriptive analysis methodology and qualitative research methods, this study focuses on former drug users receiving treatment at "Rumah Kita." The goal is to comprehend the Eucharistic meaning for those in the process of healing and to examine the ways in which this meaning influences their spiritual and social development. As a transforming experience, a wellspring of spiritual fortitude, and a healing community for the celebration of new life, the Eucharist functions as a comprehensive encounter. Addicts who have taken drugs believe that attending Eucharistic celebrations makes them more conscious of their transgressions. Through the love of the Father, they are fully formed and prepared to face the outside world. For those overcoming addiction who are working toward recovery, the Eucharistic celebration transforms into a profoundly holistic experience.AbstrakPecandu narkoba sering dipandang sebagai manusia yang rusak secara moral, spritual, dan fisik. Kehadiran rehabilitasi narkoba “Rumah Kita” yang di kelola para suster KSSY, menjadi sarana yang memberikan pendampingan pastoral. Rumusan penelitian: Perayaan Ekaristi menjadi perjumpaaan holistik terhadap pemulihan adiksi narkoba. Metode penelitian menggunakan penelitian kualitatif dengan desain analisis diskriptif terhadap mantan adiksi narkoba di rehabilitasi “Rumah Kita”. Tujuannya untuk mengetahui makna Ekaristi bagi individu yang menjalani pemulihan dan menganalisis bagaimana makna tersebut berkontribusi terhadap traspormasi sosial dan spritual mereka. Ekaristi menjadi perjumpaan yang holistik yakni pengalaman trasformatif, sumber kekuatan spritual, dan komunitas penyembuhan untuk perayaan hidup baru. Korban adiksi narkoba merasa bahwa perayaan Ekaristi membawa mereka pada kesadaran akan keberdosaanya. Kasih Bapa merangkul mereka untuk menjadi manusia yang utuh dan siap menghadapi dunia baru. Perayaan ekaristi menjadi sarana perjumpaan holistik yang mendalam bagi korban adiksi yang berjuang untuk pulih.